Quantitative Detection of Amino Acids and Carnitine in Human Blood and Quality Control of Peptide Drugs - Yuchun Ma; Yujie Zhu; Zhengqing Lu; Huiqing Hu; Jinmei Li; Shangqing Yang; Jiaru Han (Journal of Chemistry)
In order to deal with the biochemical metabolic disorder and the lack of end metabolites caused by hereditary metabolic diseases, a quantitative detection method of amino acids and carnitine in human blood and the quality control method of polypeptide drugs were proposed. First, a method for the detection of 10 amino acids and 32 acylcarnitine metabolites in human blood was established and analyzed by liquid chromatography tandem mass spectrometry. Through the experimental research on typical peptide drugs, combined with the classical synthesis process and the PLS-DA model of human body in different regions, the relevant detection methods for the quality control of peptide drugs were established, which provided a reference for the formulation of peptide drug quality standards. The experimental results show that the quantitative detection method proposed in this paper can effectively detect the content of most amino acids and acylcarnitine. The classical detection method achieved a loss of 16.74% smaller mass-to-charge ratio, and based on this, the quantitative standard for polypeptide drug delivery was determined, which verifies the correctness and superiority of the detection method in this paper.